Pengembangan Instrumen Tes Matematika pada Materi Statistika Berbasis Kontekstual untuk Siswa Kelas VII SMP (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to develop a contextual learning-based mathematics test instrument focused on Statistics and intended for eighth-grade junior high school (SMP) students. The instrument developed consists of essay questions designed by integrating real-life situations to make them more relevant and meaningful for students. This contextual approach is expected to help students understand statistical concepts more deeply and improve their ability to solve mathematical problems related to everyday life. In the instrument development process, a series of analyses were conducted to test the quality of the test items, including validity, reliability, discriminating power, and difficulty level. The validity of the test items was tested using the correlation between item scores and total scores, with the results showing that all test items had a correlation coefficient greater than the r value of the table, thus being declared valid. Meanwhile, the reliability coefficient obtained was 0.84, indicating that this instrument has a high level of consistency and is suitable for use in measurement. Analysis of the discriminating power showed that each test item had excellent ability to differentiate students with high and low abilities. The analysis of the difficulty level showed balanced variations, namely from easy, medium, to difficult categories. This variation is important to accommodate differences in student ability levels and reflect the diversity in the context of the problems presented. Overall, the results of this study indicate that the developed test instrument is of excellent quality and can be used as an evaluation tool to measure students' mathematical problem-solving abilities. Furthermore, this instrument supports more contextual, interactive, and meaningful statistics learning.